2011
DOI: 10.1111/j.1475-1313.2011.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of visual degradation on face discrimination

Abstract: Poor face discrimination has a profound impact on real-life social communication. Here we report that artificial visual degradation also adversely impacts a synthetic face recognition task. As a rule of thumb, reduction in VA of 0.3 logMAR (halving the decimal VA) reduces the face recognition distance by a factor of 0.6 times. The FrACT-based face discrimination task provides an efficient new tool to quantify and monitor face discrimination ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
1
28
1
Order By: Relevance
“…Our results are consistent with McCulloch et al (2011) andOwsley et al (1981) in showing that manipulating perceptual signal strength influences face processing in aging. Cronin-Golomb et al (2007) found that enhancing or degrading stimulus contrast did not influence performance of YA and OA on the Benton Face Recognition Test (BFRT).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results are consistent with McCulloch et al (2011) andOwsley et al (1981) in showing that manipulating perceptual signal strength influences face processing in aging. Cronin-Golomb et al (2007) found that enhancing or degrading stimulus contrast did not influence performance of YA and OA on the Benton Face Recognition Test (BFRT).…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with our findings with LSF faces and suggest that reducing signal strength may or may not produce age-related effects depending on the type of image manipulation employed. Unlike the present study and those by McCulloch et al (2011) andOwsley et al (1981), Cronin-Golomb et al (2007) included acuity as a covariate in their analysis. Further discussion is needed on whether basic measures of vision should be included as covariates in studies on visual cognition.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Nevertheless, some studies, using different experimental designs to the one reported here, disagree that contrast sensitivity is important for face recognition and suggest that loss of VA is more debilitating. 17,18,44,51 All the same, the participants in our sample had relatively good acuity (6/9 or better), so it is possible that these results are underestimating the true impact of VA loss on facerecognition performance. It is also important to note that the central 10-2 IVF and PRlogCS accounted for less than half of the variation in facial-recognition performance (R 2 ¼ 39%).…”
Section: Discussionmentioning
confidence: 76%
“…Yet, obviously, these features will play some role in real-life face recognition. Still, the CFMT is a validated test that has been used in a variety of clinical situations 33,51,52 and was developed based on the strengths of other face-recognition tests that were already widely used in research. The test also simulates how faces would be learned in the real-world, by allowing participants to gradually acquire information about the faces from a variety of different viewpoints and build up more detailed representations in memory.…”
Section: Discussionmentioning
confidence: 99%